Laryngopharyngeal reflux: current perspectives and controversies - Kryshtal, V. M.; Melnikova, O. V.; Khorolets, O. V.; Hancheva, O. V. (Modern medical technology, 2025)
The aim of this study is to systematize current concepts and describe key pathogenetic variants of laryngopharyngeal reflux formation based on the analysis of recent experimental research and clinical observations. Materials and methods. The study examined pathogenetic mechanisms of laryngopharyngeal reflux (LPR) formation using methods of analysis, synthesis, and generalization of scientific data. The information base was formed through a systematic literature search in international scientometric databases, in particular PubMed, Scopus, Web of Science, and Google Scholar. A total of 90 sources were selected for further analysis according to criteria of scientific significance (high journal quartile, authors’ h-index, and statistical validity). The search strategy included the identification of the topic’s relevance, formulation of appropriate queries (laryngopharyngeal reflux, vagus reflex, autonomic nervous system, etc.), critically assessing the reliability of sources, comparing results between studies, and summarizing the data obtained. Results. The literature review revealed that LPR is a multifactorial, complex, and poorly standardized syndrome with a wide range of nonspecific symptoms. Theoretical analysis identified four principal pathogenetic mechanisms of LPR: chemical (microaspiration and mucosal damage), neuro-reflex (hypersensitivity), muscular (laryngeal overload), and immunobiological (chronic inflammation and microbiota imbalance). LPR may result from esophageal motility disorders, sphincter dysfunction, neuroimmune and psychovegetative disturbances while its chronicity is promoted by central and peripheral sensitization, stress, genetic predisposition, and behavioral factors including obesity, smoking, diet, and medication. It was established that there is no universal diagnostic standard for LPR, and current diagnostic approaches remain complex and fragmented, relying largely on the exclusion of other pathologies and empirical treatment. Conclusions. The complex and heterogeneous pathogenesis of laryngopharyngeal reflux accounts for its symptoms variability. Identification of distinct pathogenetic variants or typical phenotypes with specific clusters of morphological, structural, functional, biochemical, instrumental, and psychometric features will facilitate the development of highly effective integrative pharmacological treatment approaches.